Athletes’ Mental Toughness: Gender, Type of Sport, and Competition Experience - Arzaqi, Anindhya Faza; Rahayu, Iin Tri; Nuqul, Fathul Lubabin (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Abstract. An athlete's success or failure is influenced by many factors. However, behind every challenge, mental toughness is the main key. This study aims to determine the profile or description of mental toughness of athletes in terms of gender, type of sport, and athlete competition experience. This study uses a quantitative approach with a correlational method. The research sample consisted of 100 athletes from seven sports. The research was conducted using an accidental sampling technique. Data collection was carried out using a modified scale from the Sports Mental Toughness Questionnaire (SMTQ). The results showed that there were significant differences in mental toughness based on gender, sport, and athlete competition experience (all: P<0.05). Male athletes tend to have higher mental toughness than female athletes. In the sports of football, volleyball, badminton, and table tennis have higher mental toughness than the sports of Sepak Takraw, basketball, chess. Whereas in athletes with higher level of competition experience, they also tend to have higher mental toughness. This finding can be concluded that male athletes with high competition experience from the sports of soccer, volleyball, badminton, and table tennis tend to have higher mental toughness than female athletes who have not had competitive experience from the sports of basketball, Sepak Takraw, and chess. Therefore, it is important to consider such factors in training and mental development programs to improve their overall performance. Keywords: Mental Toughness, Athletes, Sports